2010
DOI: 10.1051/fruits/2010023
|View full text |Cite
|
Sign up to set email alerts
|

Free carotenoid and carotenoid ester composition in native orange juices of different varieties

Abstract: Free carotenoid and carotenoid ester composition in native orange juices of different varieties.Abstract -Introduction. Among the citrus species, C. sinensis has been the most studied given its importance in terms of production and its industrial application in juices. Some of orange juice's organoleptic and functional properties, which make it an attractive product for the consumer, are due to its carotenoid composition. Xanthophylls can be found in either their free form (as the carotenes are found) or in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 38 publications
6
27
3
Order By: Relevance
“…These results were in accordance with those reported by Guiffrida et al (2010), who also found that the major xanthophylls, regardless of the blood orange variety, were cis-violaxanthin and β-cryptoxanhtin (Giuffrida, Dugo, Salvo, Saitta, & Dugo, 2010). In grapefruit juice, lycopene was the major carotene and represented 80% of the total amount (β-carotene represented the other 20%).…”
Section: Accepted M Manuscriptsupporting
confidence: 82%
“…These results were in accordance with those reported by Guiffrida et al (2010), who also found that the major xanthophylls, regardless of the blood orange variety, were cis-violaxanthin and β-cryptoxanhtin (Giuffrida, Dugo, Salvo, Saitta, & Dugo, 2010). In grapefruit juice, lycopene was the major carotene and represented 80% of the total amount (β-carotene represented the other 20%).…”
Section: Accepted M Manuscriptsupporting
confidence: 82%
“…Moreover, it is well known that the main xanthophylls in ripening citrus fruits are esterified with fatty acids conferring a greater compound stability (Gross 1987). In mature fruit tissues of sweet oranges and grapefruits, the percentage of xanthophylls esterified is variable, but can reach up to 85-90 % of the total (Philip 1973a, b;Gross 1987;Giuffrida et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic hydrolysis with other lipases, without previous sample cleanup by open column chromatography, was successfully applied to remove diacylglicerides and triacylglycerides from paprika oleoresin and krill oil aiming at determining the natural carotenoid profile of these samples [7]. On the other hand, no pre-treatment was carried for analysis of carotenoid esters from orange juices [8] and from tropical fruits from Panama [9]. Alternatively, two-dimensional comprehensive liquid chromatography coupled to mass spectrometry can be used to improve the separation of the carotenoids in their native form, facilitating the identification [10,11].…”
Section: Introductionmentioning
confidence: 99%